Supporting and empowering students in online pre-calculus - Golden, Shannon Nicole, author; Hagman, Jess, advisor; Balgopal, Meena, committee member; Hulpke, Alexander, committee member (Colorado State University. Libraries, 2020)
The Paced Algebra to Calculus electronically Program (PACe) offers pre-calculus through five 1-credit courses in a fully online and mastery-based setting. The mathematics department at Colorado State University realized that a significant population of students were not completing the first module in the sequence. To address this issue, we created an in-person, supplemental course for a targeted population of students to complete the first 1-credit pre-calculus course. Using data from the students' weekly metacognitive and mindful journaling, we use the emergent perspective as our theoretical lens and thematic analysis as our tool for data analysis to answer the following research question: how did participation in an in-person class and engagement with the PACe Program impact the students' mathematical affect and success in the course? In this paper, we will examine previous results in the literature, define our research methodology, analyze implications on teaching, share key results and findings, and discuss future research questions that could be answered with our data.
Keywords: mathematical affect; PACe; supplemental instruction; online instruction; agency; pre-calculus